2021
DOI: 10.1111/jsap.13342
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in dogs with chronic liver disease

Abstract: Objectives To assess platelet function, buccal mucosal bleeding time and plasma von Willebrand factor concentration in dogs with chronic inflammatory and/or fibrotic liver disease and to compare results with those obtained in healthy dogs. Materials and Methods Preliminary study including 18 dogs with chronic inflammatory and/or fibrotic liver disease undergoing liver biopsy and 18 healthy age‐matched control dogs. Platelet function was assessed by measuring closure time with the PFA‐100® analyser using adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 113 publications
(248 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, Wilkinson et al . (2021) found that mean vWF antigen concentrations in their population of dogs with chronic hepatopathies were higher than those of an age‐matched healthy control population; however, the difference was not significant. Importantly, their study may have been underpowered to detect this difference.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Interestingly, Wilkinson et al . (2021) found that mean vWF antigen concentrations in their population of dogs with chronic hepatopathies were higher than those of an age‐matched healthy control population; however, the difference was not significant. Importantly, their study may have been underpowered to detect this difference.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Wilkinson et al . (2021) discussed that ADP may be unable to detect platelet function defects if these defects are a consequence of storage pool defects that affect ADP content in dense granules. In this case when adding ADP to the sample, the defect would be corrected producing a normal result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations